2018
DOI: 10.3389/fchem.2018.00635
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Natural Nanostructured Rods and Platelets on Mechanical and Water Resistance Properties of Alginate-Based Nanocomposites

Abstract: A series of biopolymer-based nanocomposite films were prepared by incorporating natural one-dimensional (1D) palygorskite (PAL) nanorods, and two-dimensional (2D) montmorillonite (MMT) nanoplatelets into sodium alginate (SA) film by a simple solution casting method. The effect of different dimensions of nanoclays on the mechanical, water resistance, and light transmission properties of the SA/PAL or MMT nanocomposite films were studied. The field-emission scanning electron microscopy (FE-SEM) result showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The control film showed bands at 3423 cm −1 for the O-H stretching vibration, at 2929 cm −1 for the C-H stretching, between 1645 and 1452 cm −1 for the asymmetric and symmetric stretching of -COO-, and a band of approximately 1080 cm −1 , which was assigned to a mannuronic unit [ 18 , 32 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The control film showed bands at 3423 cm −1 for the O-H stretching vibration, at 2929 cm −1 for the C-H stretching, between 1645 and 1452 cm −1 for the asymmetric and symmetric stretching of -COO-, and a band of approximately 1080 cm −1 , which was assigned to a mannuronic unit [ 18 , 32 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Within these materials is sodium alginate, a salt of alginic acid that is isolated from brown algae and can be synthesized by microorganisms. It is considered an inexpensive, non-toxic, biodegradable, and biocompatible biopolymer that is safely used in food as a thickener, gelling agent, and emulsion stabilizer [ 17 , 18 ]. On the other hand, propolis is a resinous mixture of substances collected and used by bees to protect the entrance of the hive.…”
Section: Introductionmentioning
confidence: 99%
“…Bogdanović et al [30] showed that hematite nanofiller has an influence on the improvement of the mechanical properties of an epoxy polymer matrix when the composites are prepared with low filler content (up to 1 wt.%). There is a possibility for the agglomeration of filler particles in the polymer matrix when the filler content exceeds a certain value, which influences the decrease in the mechanical properties [31]. This can be observed for the values of tensile strength for LDPE/1%HE2, LDPE/0.5%HR1 and LDPE/1%HR1 samples.…”
Section: Mechanical Propertiesmentioning
confidence: 95%
“…Biopolymer based nanocomposite films, which consist of single dimensional palygorskite (PAL) nanorods and double dimensional montmorillonite (MMT) nanoplatelets in the sodium alginate (SA) film resulted in an enhancement in the tensile stress and the capacity of water resistance of the film (Huang et al, 2018).…”
Section: Improvement In Desalination Performance Of Tfnsmentioning
confidence: 99%